2008
DOI: 10.1110/ps.036426.108
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical studies of TREX1 inhibition by metals. Identification of a new active histidine conserved in DEDDh exonucleases

Abstract: TREX1 is the major exonuclease in mammalian cells, exhibiting the highest level of activity with a 39!59 activity. This exonuclease is responsible in humans for Aicardi-Goutières syndrome and for an autosomal dominant retinal vasculopathy with cerebral leukodystrophy. In addition, this enzyme is associated with systemic lupus erythematosus. TREX1 belongs to the exonuclease DEDDh family, whose members display low levels of sequence identity, while possessing a common fold and active site organization. For these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…We demonstrate that lithium and sodium inhibit the exonucleolytic activity of Trex1 by inducing subtle rearrangements in active centers. Our analysis also revealed that a histidine residue (His124), highly conserved in the DEDDh family, is involved in the activity of Trex1 (15).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…We demonstrate that lithium and sodium inhibit the exonucleolytic activity of Trex1 by inducing subtle rearrangements in active centers. Our analysis also revealed that a histidine residue (His124), highly conserved in the DEDDh family, is involved in the activity of Trex1 (15).…”
mentioning
confidence: 63%
“…For quantitative RT-PCR analysis, RNA was treated with DNAse (Roche) to remove contaminating DNA. For cDNA synthesis, 1 mg RNA and Moloney murine leukemia virus RT RNase H Minus, Point Mutant, oligo(dT) 15 primer and PCR nucleotide mix were used, following the manufacturer's instructions (Promega Corporation, Madison, WI). The primers used to amplify murine Trex1 cDNA were 59-CGTCAACGCTTCGATGACA-39 and 59-AGTCATAG-CGGTCACCGTTGT-39.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…Enzymes of the DEDD 39→59 exonuclease superfamily (also named the DnaQ superfamily) are characterized by four acidic residues, three Asp (D) and one Glu (E), distributed over three separate sequence segments (Exo I, Exo II, and Exo III; Moser et al, 1997;Zuo and Deutscher, 2001). Residues from this DEDD motif constitute binding sites A and B for two divalent metal ions that are essential for the catalysis of nucleoside monophosphates at DNA or RNA termini in the 39→59 direction (Derbyshire et al, 1995;Brucet et al, 2008). Besides the substrate-binding sites, the presence of either Tyr or His at the active sites defines the DEDDy or DEDDh family, respectively.…”
Section: A2mentioning
confidence: 99%
“…TREX1 activity has a propensity toward certain DNA sequences and requires magnesium and manganese in the active site for proper functioning (5). In humans, mutations in TREX1 are associated with the Aicardi-Goutières syndrome (AGS), a neurologic disease characterized by chronic production of IFN in the CNS (6).…”
mentioning
confidence: 99%